Multimodality MRI Findings in Patients with End-Stage Renal Disease. - Chen, Hui Juan; Zhang, Long Jiang; Lu, Guang Ming (BioMed Research International, 2015)
Patients with end-stage renal disease (ESRD) suffer from a number of complex neurological complications including vascular damage and cognitive dysfunction. It is of great significance to detect the neurological complications and improve the prognosis of ESRD patients. Many new noninvasive MRI techniques have been steadily used for the diagnosis of occult central nervous system complications in ESRD patients. This gives an opportunity to understand the pathophysiological mechanisms of these neurological disorders. This paper is a review that presents the MRI findings of occult brain damage in ESRD patients, outlines the applications of advanced MRI techniques, and introduces a brief perspective in this study field.